New personal names from the point of view of derivation and semantics - Murmulaitytė, Daiva (Lietuvių kalba, 2016)
The paper discusses the results of a pilot study into derivational patterns and semantics of some neologisms referring to persons given in the Database of Lithuanian Neologisms (further also DLN). The research focused on nouns ending in -tojas, -a, -ėjas, -a, -ikas, -ė, ‑ininkas, ‑ė, ‑ėlis, -ė, -ūnas, -ė and -uolis, -ė. Most of these words are suffixal derivatives usually attributed to the categories of nomina agentis, nomina attributiva and nomina professonalia. The analysed suffixes are very different in their productivity. The suffixes -ininkas, -ė, -tojas, -a, -uolis, -ė are very productive, whereas the suffix -ėjas, ‑a, in Lithuanian grammars treated as one of the most typical and productive agentive suffixes, in the DLN have only been attested in a couple of words. The paper also discusses when a new phenomenon should be treated as a neologism and when it is merely a new sense of the existing word, included in some key publications based on the DLN. The investigation draws a conclusion that when analysing current situation and tendencies of word-building the formal principle of classifying neologisms is not operational. According to it, a compositional neologism coinciding with the already existing word is treated as a word with a new sense rather than a neologism. However, in cases when a new lexeme of an already existing word emerges as a result of a new derivational opposition, by building a word from a new or already existing lexeme of the base word, the new lexeme should be treated as a neologism rather than a new sense of the existing word. New senses (semantic neologisms) emerge in cases of semantic development of the word as a result of meaning transfer, lexicalisation and other processes. Another aspect of the present investigation focuses on the relationship between lexical senses and senses of individual derivation. An attempt was made to identify if lexical and derivational senses were the same or whether the former was narrower or broader than the latter. If they were not the same, causes of their divergence were identified. The latter issue might be relevant when analysing further processes of neologism lexicalisation. The paper also attempts to clarify the derivational patterns (origin) of some concrete neologisms and their semantic structure. Such interpretations are appreciated and very welcome by lexicographers, who are responsible for appropriately presenting neologisms in lexicographic publications. Alongside derivatives, analogous, mixed, contaminative formations as well as translations have been discussed. These derivative and formal aspects of neologisms might turn out to be very important in further investigation of larger and more varied groups of affixal derivatives and identifying general features of contemporary word-building. In pursuing the main goal of the investigation, an attempt was also made to discuss in more detail the DLN as a source of new Lithuanian lexis. It has been noticed that the DLN lacks a number of neologisms which are base words for the ones given in the database. They have all been attested on the internet. Such base words in the DLN would help define their derivatives without repeating the information which is inevitably given in the definition of the base word. Seeking precision, some definitions of the neologisms should be revised; for example, definition patterns of nouns should not be used to define adjectives. In some cases, a neologism given in the DLN as a single lexeme should be presented as two different lexemes, for example, the word pilstukininkas, –ė ‘someone who sells or drinks low quality home-brewed alcohol’ should be given as two lexemes representing two derivational categories: nomina professonalia and nomina attributiva. One of the goals of the investigation was concerned with exploring further prospects of researching the derivation of neologisms, posing the key questions and verifying their relevance. Presumably, the results of the investigation could be used in researching the tendencies of deriving neologisms in contemporary Lithuanian and comparing them with the tendencies described in the grammars of Lithuanian of the 2nd half of the 20th century. It would be interesting to ascertain how derivational patterns of neologisms are changing, when the lexicon is inevitably changing due to an enormous flow of information, more intensive communication in smaller communities and in the world, due to new emerging mass media and under the influence of other languages, especially English, which is structurally much more distant than Russian, a language having influenced Lithuanian several decades ago. (Translated by Inesa Šeškauskienė).